Antibacterial effect of bioactive glass incorporated in acrylic resins against Streptococcus mutans and Lactobacillus acidophilus activity in biofilm - Özer, Hazal; Özcan, Mutlu (Brazilian Dental Science, 2022)
Objective: The rough surfaces of removable appliances used in pediatric dentistry or orthodontics, may result inan environment for biofilm accumulation, yielding to enamel demineralization. This study aimed to assess theeffects of adding nanoparticles of bioactive glass to polymethylmethacrylate to promote the antibacterial activityin acrylic resins. Material and Methods: Acrylic resin specimens (20x20x1mm3) were prepared by adding 2% or5% bioactive glass. The specimens in the control group without bioactive glass were prepared from the mixtureof acrylic powder containing nanoparticles and liquid monomer (n=10 per group). The antibacterial activity ofthe specimens against Streptococcus mutans and Lactobacillus acidophilus activity in biofilm was investigatedthrough counting colony forming units (CFU). Data were analyzed using a one-way analysis of variance andTukey’s post hoc tests at the significance level of 0.05. Results: The incorporation of 2% (p=0.001) and 5%(p